Rastreamento do ponto de máxima potência de turbinas magnus acionando geradores elétricos - Ribeiro, Cláudia Garrastazu (2014)
The constant human need for electricity, as well as the increasing demand for energy causes the use of finite sources, as oil and coal. The search for alternative energy sources as wind harvesting is the motivation for this master dissertation. Wind energy is a consolidated technology, mostly based on three blades wind turbine. This master thesis constitutes an analysis of a non-conventional wind machine, named Magnus wind turbine. The turbine s operation is based on the Magnus effect and its difference with respect to the traditional type is that it has rotating cylinders instead of fixed blades, which benefits an increase of generated power, since this turbine can produce power from low wind speeds. A method to track the maximum power point based on the control of the cylinders rotation is proposed, whereas in literature only fixed values were found for this variable. This Magnus turbine is used to drive a permanent magnet synchronous generator as a way to prove the theoretical predictions. The electrical generator also uses a specific method to track the maximum power point for the whole set. Simulated and practical results are demonstrating the performance of the Magnus wind turbine driving a permanent magnet synchronous generator.